Seasonal feeding behavior and forage selection by goats in cleared and thinned deciduous woodlands in Northeast Brazil. - MESQUITA, R. C. M. (1985)
Abstract: The seasonal feeding behavior, forage preferences and body weight responses of goats were studied under three densities of woodland (called castings), and under three stocking rates. The experiment was located in the semi-arid tropics of northeastern Brazil at 3 42' South latitude, and 40 21' West longitude at an elevation of 75 meters. Mean annual precipitation of the area is 832 MI. Removing the shrubs and trees increased yields of herbaceous only on partially-cleared sites. Goats gained body weight (kg BW/ha) during the wet season, with the cleared treatment showing the best body weight response per unit of land. However during the dry season, animals lost weight probably due the low quality and quantity of available forage. The botanical composition of goats' diets showed them to be nixed feeders, consuming grasses, forth, and browse in various combinations depending on the season and the array of forage species available. During the dry season standing hay from herbaceous species and regrowth of some woody evergreen species were the principal forages. Animals maintained body weight on this forage. However, leaf litter was an important component of goats' diets during the dry season, but was inadequate for weight maintenance. Goats in all treatments spent the least time grazing during the wet season and the most time during the beginning of the dry season. They spent the most time lying ruminating during the dry season and the least time during the wet season. Forage quality was probably a limiting factor to effective animal response during the dry season. Goats exhibited dislike for rain and wet conditions. They grazed freely when the temperatures were high (35 to 39 C). However, periods of high temperature corresponded to periods of low relative humidity, perhaps moderating the discomfort factor of combined high temperatures and high humidity.